Local community participation in sustainable tourism planning of Malaysian protected areas. - Abdul Gani, Arni; Awang, Khairil Wahidin; Samdin, Zaiton; Mohd, Abdullah (2012)
Local community participation has been acknowledged by many researchers as key factors towards achieving sustainable development in protected areas. However, recreation and tourism planning especially in protected areas; often exist in seclusion from the elements that constitute social, environmental and economic aspects of the area. Thus, conflicts may arise between park management and the community such as conflict between different user groups and competing usage of the same scarce resource which eventually lead to much serious problems such as environmental degradation. Community participation in decision making is one approach to establish a sense of belonging that is important for general well-being and support sustainable development. This could bring positive outcome and active participation would enable park management and the authorities to develop new attractions in the park and offer more sustainable forms of recreation and tourism which suit the people. However, the ability to maintain a healthy environment and economy and to pursue a participatory democracy requires effective management of public involvement. In addition, it also requires understanding not only the conditions that may have the potential to create conflicts but most importantly is to comprehend what are the conditions that can promote a cooperative relationship among the local people and the park management and authorities. This paper outlines the human dimensions of local peoples' participation and also discusses on the approaches towards promoting effective involvement of local community in the decision making process in planning for tourism and recreation in protected areas.